The Importance of the Journey Map in the Design of a Playful Interactive-Interface (Global Journal of Management and Business Research, 2021)
This article presents the importance of using the customer journey map (CJM) as a tool for managing new information technologies. The case study presents the use of the CJM to indicate the experiences that people have when using a playful interactive-interface, where the causal relationship between the brightness and the distance of the stars is visualized. The CJM is the result of a quantitative and qualitative study about user experience (UX) or UX research. Where you can use: 1) observation techniques, 2) interviews, 3) questionnaires, 4) a review of the domain literature about the phenomenon, archetypal descriptions, 5) diagrams of mental models; also known as thought schemes, or cognitive maps, among others. This research focuses the development of the interface in the design of archetypal profiles and mental models to generate the CJM, in the domain of the specific phenomenon.
Keywords: customer journey map; interactive-interface; new technologies; mental model